2017
DOI: 10.1002/jsfa.8646
|View full text |Cite
|
Sign up to set email alerts
|

Non‐destructive technique for determining the viability of soybean (Glycine max) seeds using FT‐NIR spectroscopy

Abstract: The results demonstrated that the FT-NIR spectral analysis with the PLS-DA method that uses all variables or the selected variables showed good performance based on the high value of prediction accuracy for soybean viability with an accuracy close to 100%. Hence, FT-NIR techniques with a chemometric analysis have the potential for rapidly measuring soybean seed viability. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 35 publications
1
47
0
2
Order By: Relevance
“…Lohumi, Mo, Kang, Hong, and Cho () explored the feasibility of using Fourier transform near‐infrared spectroscopy (FT‐NIR) combined with partial least squares‐discriminant analysis (PLS‐DA) to identify the viability of watermelon seeds. Moreover, FT‐NIR technology combined with PLS‐DA model was applied for the viability detection of crop seeds such as corn (Ambrose, Lohumi, Lee, & Cho, ) and soybean (Kusumaningrum et al, ), and the satisfactory results were achieved. In addition, HSI technology coupled with suitable model was successfully applied in the identification of viable and nonviable muskmelon seeds (Kandpal, Lohumi, Kim, Kang, & Cho, ), wheat (Zhang et al, ), and other seeds.…”
Section: Introductionmentioning
confidence: 99%
“…Lohumi, Mo, Kang, Hong, and Cho () explored the feasibility of using Fourier transform near‐infrared spectroscopy (FT‐NIR) combined with partial least squares‐discriminant analysis (PLS‐DA) to identify the viability of watermelon seeds. Moreover, FT‐NIR technology combined with PLS‐DA model was applied for the viability detection of crop seeds such as corn (Ambrose, Lohumi, Lee, & Cho, ) and soybean (Kusumaningrum et al, ), and the satisfactory results were achieved. In addition, HSI technology coupled with suitable model was successfully applied in the identification of viable and nonviable muskmelon seeds (Kandpal, Lohumi, Kim, Kang, & Cho, ), wheat (Zhang et al, ), and other seeds.…”
Section: Introductionmentioning
confidence: 99%
“…This indicated that the new hyperplane in the characteristic spectral space could no longer classify the samples as the hyperplace managed to do in the full-range spectral space. The results in previous literature [12,23] showed that the performances of those models established on the selected variables had decreased slightly. However, Yang et al, (2015) showed the opposite result, where the classification rates of the SVM model based on feature wavelengths increased while using SPA methods to select the feature wavelength variables [6].…”
Section: Discriminant Models Based On Feature Wavelength Variablesmentioning
confidence: 86%
“…Applying appropriate methods to select feature wavelengths for modeling would obtain the same performance as the full-range wavelength models in seed quality detection [23,35]. In this study, the genetic algorithm (GA) was utilized to identify the feature wavelengths.…”
Section: Feature Wavelengths Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Цвет является довольно устойчивым генетически и наиболее простым в измерении биофизическими мето-дами феномаркером для контроля качества семян. Оптическая технология сепарации семян, согласно обширным исследованиям [25,28,31,32,33,34,36,38,39,40,42,43,44,45,46,47,49], способна определять происхождение и жизнеспособность репродуктивного материала. При необходимости нетрудно реализовать и классификацию семян по количественному признаку, и элиминирование примесей.…”
Section: технологии машины и оборудование --------------------------unclassified